FACTORES PARA MEJORAR LA CALIDAD DEL APRENDIZAJE DEL ESTUDIANTE UNIVERSITARIO - Rodríguez del Solar, Natalia (2014)
In the "knowledge age", the most important educational activity is the one of "learning". The student ability to "learn" goes along with her/him for life. Thanks to "learning" the human being can increase, develop and perfect knowledge, competencies, skills, and character in order to live a successful and worthy life. We, the Faculty, share the mission to educate and develop competent professionals who will contribute to the sustainable development of the country (Peru) and of the world. Facing this critical commitment, we have payed close attention through our research to the key quality factors in order to enhance the "learning process" of the college student. In our research we have proved that the key elements for enhancing the "System for orientation and learning" process are: a) The student, b) The professor/facilitator, c) The didactic strategies, d) The media tools (video, audio, objects, images, sounds, etc), e) The classroom harmony and f) The evaluation process. All these are the key factors for the "learning process" enhancement. We have proved which factors are most important and in which cases. Finally we have enriched our study taking into account valuable feedback from professor and students from undergraduate and graduate programs.